Analisis Ketersediaan Sarana dan Prasarana Pendidikan Jasmani di SD Gugus IV Kabupaten Soppeng. - Muliadi Muliadi; Sudarto Sudarto; Mujahidah Mujahidah; nurul khumairah (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The problem in this study is how the availability and condition of physical education facilities and infrastructure in elementary school cluster IV Soppeng Regency. This descriptive qualitative research aims determine the availability of physical education facilities and infrastructure because affects students mastering the learning material. Data analysis techniques are data reduction, data presentation, conclusion. The results of this study indicate that the facilities and infrastructure of Physical Education in SD Cluster IV, Soppeng Regency are still not supportive enough to carry out Physical Education lessons properly.